2006
DOI: 10.1177/0020764006065155
|View full text |Cite
|
Sign up to set email alerts
|

Personal Tragedy or System Failure: A Qualitative Analysis of Narratives of Caregivers of People with Severe Mental Illness in Hong Kong and Taiwan

Abstract: To reduce such experiences, this paper calls for inclusive policies for the family, new education strategies and reflections on the roles of mental health professionals in empowerment and advocacy beyond conventional treatment, counseling and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The views of carers and health or social care professionals are at times at odds with each other and, to resolve these differences, professionals must engage with carers rather than criticise them for not conforming to professional assumptions (Small et al, 2010). Chiu et al (2006) found that the sense of helplessness experienced by family members was largely sustained by the healthcare system. Indeed, scarce contact between caregivers and health professionals has been shown to increase subjective carer burden (Jacob et al 1987;Chang et al, 2010cited in Hastrup et al, 2011).…”
Section: Carer Involvement and Adult Mental Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…The views of carers and health or social care professionals are at times at odds with each other and, to resolve these differences, professionals must engage with carers rather than criticise them for not conforming to professional assumptions (Small et al, 2010). Chiu et al (2006) found that the sense of helplessness experienced by family members was largely sustained by the healthcare system. Indeed, scarce contact between caregivers and health professionals has been shown to increase subjective carer burden (Jacob et al 1987;Chang et al, 2010cited in Hastrup et al, 2011).…”
Section: Carer Involvement and Adult Mental Healthcarementioning
confidence: 99%
“…Ostman and Kjellin (2002 noted that relatives who acted as carers had deep-seated feelings of inferiority to staff, which could explain low levels of cooperation between relatives and professionals as well as subsequent difficulties with access to services (cited in Gray et al, 2009). Lack of carer involvement reinforced the view of some professionals that silence means acquiescence / acceptance (Chiu et al, 2006).…”
Section: Carer Involvement and Adult Mental Healthcarementioning
confidence: 99%
“…Blaming oneself for causing the illness or contributing to its development (Chiu, Wei and Lee, 2006;Harden, 2005;Lefley, 1996;Milliken, 2001;Pejlert, 2001). Despite the well-recognised and widely promoted biomedical aetiology of serious mental illness such as schizophrenia and bipolar disorder, family caregivers commonly retain a sense of responsibility at some level for mental illness developing in their loved one.…”
Section: Caregiver Narratives In Mental Illness -Burden Versus Gainmentioning
confidence: 99%
“…Studies continue to support the fact that families affected by mental illness experience burden and more still needs to be done to help family members build long-term resiliency to successfully cope and adapt (Stjernswrd & Ostman, 2008;Chiu, Wei, & Lee, 2006). The outlier with the low pre-resilience score and the two participants whose resilience scores declined following participation in SFT also support this argument and the need for effective interventions to not only decrease burden but to increase resiliency.…”
Section: Discussionmentioning
confidence: 97%
“…Roick et al (2006) and Rossler et al (2005, p. 401) found a patients symptoms adversely affects family burden with "psychosis [was] ranked the third most disabling condition, higher than paraplegia and blindness, by the general population." The research also notes differences in family burden based on a variety of other demographic variables including socio-economic status plus regional and cultural differences (Chiu, Wei, & Lee, 2006;Johnson, 2000;Magana, Garcia, Hernandex, & Cortaz, 2007;Roick, et al" 2006), which were not considered in the SFT study.…”
Section: Methodsmentioning
confidence: 99%